El espíritu de la lengua y las políticas de sus disciplinas en el siglo XIX alemán - Ennis, Juan Antonio (2019)
Diving in a textual corpus related to the emergency and consolidation of philology and linguistics in Germany between the beginnings of the 19th Century and the 1860s, this paper proposes to examine how language representations in these discourses handle on the basis of the separation of body and spirit and that of the sacred and the profane. This should contribute to make visible how both disciplines take part in a process of secularization through which the secular religion of the nation emerges, taking language as a central device in its political construction.